2010
DOI: 10.1148/radiol.10091636
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Minimally Acceptable Interpretive Performance Criteria for Screening Mammography

Abstract: This study identified minimally acceptable performance levels for interpreters of screening mammography studies. Interpreting physicians whose performance falls outside the identified cut points should be reviewed in the context of their specific practice settings and be considered for additional training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 13 publications
0
69
0
2
Order By: Relevance
“…To achieve higher sensitivity while lowering false-positive rates, further studies need to elucidate the interrelationships between training, experience, volume, and performance measures. Several requirements may need to be considered simultaneously, such as minimum volume in addition to combined minimum performance requirements ( 36 ). year, which makes it diffi cult to measure sensitivity accurately in this group ( 33 ).…”
Section: Breast Imaging: Infl Uence Of Annual Interpretive Volume On mentioning
confidence: 99%
“…To achieve higher sensitivity while lowering false-positive rates, further studies need to elucidate the interrelationships between training, experience, volume, and performance measures. Several requirements may need to be considered simultaneously, such as minimum volume in addition to combined minimum performance requirements ( 36 ). year, which makes it diffi cult to measure sensitivity accurately in this group ( 33 ).…”
Section: Breast Imaging: Infl Uence Of Annual Interpretive Volume On mentioning
confidence: 99%
“…Expert radiologists reviewed and signed consent forms and completed a brief survey of their demographic and practice characteristics at the 1-day meeting. Seven of the 11 expert radiologists participated in our previous study (12) in which we set criteria for low performance in interpreting screening mammography studies. Two radiologists were members of the BCSC, and none were in practice together.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologists interpreting moderate (1001-2000) and those with high volume (>2000) had a higher sensitivity [17]. It is of interest to note that the recall rate in the United States is twice the recall rate in the United Kingdom (eg, 12.5%-14.4% vs. 7.6%), with no difference in cancer detection rate [18].…”
Section: Mammography Interpretation Benchmarksmentioning
confidence: 98%
“…The study was aimed to identify minimally acceptable performance standards for interpreting screening mammograms. They reported that a sensitivity of less than 75%, specificity less than 88% or greater than 95%, recall rate less than 5% and greater than 12%, PPV2 of less than 20% or greater than 40% and cancer detection rate of 2.5 per 1000 interpretations as indicating low performance [17]. If underperforming physicians moved into the acceptable range by additional training, detection of an additional 14 cancers per 100 000 women screened and a reduction in the number of false positive examinations by 880 per 100 000 women screened would be expected [17].…”
Section: Mammography Interpretation Benchmarksmentioning
confidence: 99%